Model Partisipasi Masyarakat Kabupaten Jepara dalam Pembentukan Peraturan Daerah (Studi Kasus Tentang Pembentukan Peraturan Daerah No. 9 Tahun 2013 Tentang Retribusi Pelayanan Pasar di Kabupaten Jepara) - Mirza Muhammad (Universitas Negeri Semarang, 2019)
The purpose of the article is to describe the model of community participation in the formation of Law no. 9 of 2013 concerning Market Service Levies and discovering the obstacles. Conducting research occurs naturally, as is in normal situations, and emphasizes description naturally. Then the approach uses Sosiogis Juridical by looking at social geographical conditions which show that intense economic competition causes the orientation of society to tend to how their efforts to meet economic needs. The bureaucracy carried out by the government has not provided space for the public. Although the procedure in establishing a local regulation on market service fees involves various elements such as representatives of market traders, the process is only limited to formality. The community participation model of the Jepara Regency in the formation of a Regional Regulation has been quite high, but in the last 5 years, there has been a decrease in the level of community participation in the formation of a Regional Regulation. The low level of community participation in the formation of local regulations is due to the absence of a forum for channeling aspirations.